2018
DOI: 10.1080/10503307.2018.1490973
|View full text |Cite
|
Sign up to set email alerts
|

Do what you say and say what you are going to do : A preliminary meta-analysis of client change and sustain talk subtypes in motivational interviewing

Abstract: This preliminary meta-analysis suggests that aggregate measures of change and sustain talk are comprised of statement subtypes that are not equally meaningful in predicting outcome following MI for addictive behavior change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 55 publications
3
29
1
Order By: Relevance
“…A second study has shown that open questions and complex reflections are associated with changes from sustain talk and change talk (and vice versa) compared to simple reflections and paraphrasing [54]. Similarly, aggregate measures of change and sustain talk may contain subtypes of language that are differentially related to outcome following MI [55,56].…”
Section: Discussionmentioning
confidence: 95%
“…A second study has shown that open questions and complex reflections are associated with changes from sustain talk and change talk (and vice versa) compared to simple reflections and paraphrasing [54]. Similarly, aggregate measures of change and sustain talk may contain subtypes of language that are differentially related to outcome following MI [55,56].…”
Section: Discussionmentioning
confidence: 95%
“…If MI works as hypothesized, by conveying a relational and technical component (Miller and Rose, 2009), there should be clear associations between the fidelity of these elements and client outcomes. Although MI therapist behaviors are commonly linked to outcomes in studies of MI (Borsari et al, 2015;Gaume et al, 2014;Gaume, Heather, Tober, and McCambridge, 2018;Grodensky et al, 2017), meta-analyses of this hypothesized association have not detected direct associations between MI elements and outcome (Magill et al, 2018;Pace et al, 2017). Indications were found, T however, for indirect pathways of associations between MI-elements and outcome; that is, through measures of client change talk or client sustain talk leading to change outcomes.…”
Section: Fidelity and Outcomementioning
confidence: 95%
“…The combination between a more directional therapy with MI has raised some concerns for internal therapist conflicts on which behavior prevails in different situations (Aviram, Westra, Constantino, and Antony, 2016;Boyer, MacKay, McLeod, and van der Oord, 2018;Moyers and Houck, 2011). Findings of fidelity to MI by previous versions of the MITI in these combined settings are mixed (Magill et al, 2018;Aviram et al, 2016;Boyer et al, 2018). The risk of even larger variation in fidelity to MI in combined settings is evident and, thus, measuring fidelity in these treatment approaches is important.…”
Section: Combined With Other Therapiesmentioning
confidence: 99%
See 2 more Smart Citations